Novel 3DOM BiVO4/TiO2 nanocomposites for highly enhanced photocatalytic activity. Issue 42 (28th September 2015) - Zalfani, Meryam; van der Schueren, Benoit; Hu, Zhi-Yi; Rooke, Joanna C.; Bourguiga, Ramzi; Wu, Min; Li, Yu; Van Tendeloo, Gustaaf; Su, Bao-Lian
Abstract : BiVO4 nanoparticles in the 3DOM TiO2 inverse opal structure act as a sensitizer to absorb visible light and to transfer efficiently high energy electrons to TiO2 to ensure long lifetime of photogenerated charges and keep them well separated, explaining the extraordinarily high photocatalytic performance of 3DOM BiVO4 /TiO2 nanocomposites. Abstract : Novel 3DOM BiVO4 /TiO2 nanocomposites with intimate contact were for the first time synthesized by a hydrothermal method in order to elucidate their visible-light-driven photocatalytic performances. BiVO4 nanoparticles and 3DOM TiO2 inverse opal were fabricated respectively. These materials were characterized by XRD, XPS, SEM, TEM, N2 adsorption–desorption and UV-vis diffuse (UV-vis) and photoluminescence spectroscopies. As references for comparison, a physical mixture of BiVO4 nanoparticles and 3DOM TiO2 inverse opal powder (0.08 : 1), and a BiVO4 /P25 TiO2 (0.08 : 1) nanocomposite made also by the hydrothermal method were prepared. The photocatalytic performance of all the prepared materials was evaluated by the degradation of rhodamine B (RhB) as a model pollutant molecule under visible light irradiation. The highly ordered 3D macroporous inverse opal structure can provide more active surface areas and increased mass transfer because of its highly accessible 3D porosity. The results show that 3DOM BiVO4 /TiO2 nanocomposites possess a highly prolonged lifetime and increased separation of visible light generated charges and extraordinarily high photocatalytic activity. Owing to the intimate contact between BiVO4 and large surface area 3DOM TiO2, the photogenerated high energy charges can be easily transferred from BiVO4 to the 3DOM TiO2 support. BiVO4 nanoparticles in the 3DOM TiO2 inverse opal structure act thus as a sensitizer to absorb visible light and to transfer efficiently high energy electrons to TiO2 to ensure long lifetime of the photogenerated charges and keep them well separated, owing to the direct bandgap of BiVO4 of 2.4 eV, favourably positioned band edges, very low recombination rate of electron–hole pairs and stability when coupled with photocatalysts, explaining the extraordinarily high photocatalytic performance of 3DOM BiVO4 /TiO2 nanocomposites. It is found that larger the amount of BiVO4 in the nanocomposite, longer the duration of photogenerated charge separation and higher the photocatalytic activity. This work can shed light on the development of novel visible light responsive nanomaterials for efficient solar energy utilisation by the intimate combination of an inorganic light sensitizing nanoparticle with an inverse opal structure with high diffusion efficiency and high accessible surface area.